The control as a necessary condition for the democratic state - Косінов, С. А. (Problems of legality, 2013)
The article analyzes the concept of the control of democracy J. Keane. Control of the public authority is considered as an element of the rule of law (constitutional control over the rule-making, administrative justice, parliamentary control over the executive branch, etc.).